THz wavefront manipulation based on metal waveguides. Issue 12 (12th July 2018) - Wu, Mengru; Lang, Tingting; Shen, Changyu; Shi, Guohua; Han, Zhanghua
Abstract: In this paper, two waveguiding structures for arbitrary wavefront manipulation in the terahertz spectral region were proposed, designed and characterized. The first structure consists of parallel stack copper plates forming an array of parallel-plate waveguides (PPWGs). The second structure is three-dimensional metal rectangular waveguides array. The phase delay of the input wave after passing through the waveguide array is mainly determined by the effective index of the waveguides. Therefore, the waveguide array can be engineered using different core width distribution to generate any desired light beam. Examples, working at the frequency of 0.3 THz show that good focusing phenomenon with different focus lengths and spot sizes were observed, as well as arbitrarily tilted propagation of incident plane waves. The structure introduces a new method to perform wavefront manipulation, and can be utilized in many important applications in terahertz imaging and communication systems.